Becoming Normal: An Analysis of Normalcy in Ken Kesey’s One Flew Over the Cuckoo’s Nest - Dina Arti Novianti (Passage, 2016)
This research paper aims to make meaning of normalcy in Ken Kesey’s novel One Flew Over the Cuckoo’s Nest. The meaning of normalcy is constructed from characters who are considered as not normal. Therefore, being not normal will be analyzed by Foucault’s idea of madness (1964) as the framework. In particular, the research analyzes textual evidences which indicate the aspects of madness. By employing a narrative approach in a qualitative method which emphasizes on the analysis of the characters in the novel, the finding reveals two main points. First, that normalcy means obedience. In this case, being obedient means being submissive toward the ward’s rules. Second, the idea of normalcy is determined by those who have power. From the analysis, it can be concluded that normalcy is not a fixed construction, it depends on those who hold the authority.Keywords: Aleph, Paulo Coelho, journey in literature, life meaning, life purpos